The Da'wah Messages as the Spiritual Marketing Approach of Islamic Fashion E-Commerce at HIJUP.COM - Melly Maulin Purwaningwulan (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2021)
Indonesian Muslim consumers are looking for functional and emotional benefits in products and seeking spiritual blessings. This trend is a challenge for Islamic fashion e-commerce in promoting its products. This study uses a qualitative approach with the type of single case study research methods. The subject of this research is Islamic fashion e-commerce HIJUP.com. Researchers selected informants in the study using purposive sampling and snowball sampling techniques. Researchers used two analysis methods in case of breakdowns: an analysis based on theoretical propositions and developing case descriptions. The study results show that in Islamic fashion e-commerce, HIJUP.com contains the contents of da'wah messages, precisely, Look Good, Feel Good, Do Good. The da'wah message includes a philosophy that leads to obedience to Allah SWT concept. The message structure uses conclusion drawing and order of presentation. The message display in HIJUP.com is high-tech but straightforward techniques. The message format is unique, with interests in story or narrative and visual elements. The source of the message uses brand ambassadors, influencer marketing, and also buzzers. The study concludes that the da'wah message conveyed by Islamic fashion e-commerce includes aqidah, sharia, and morals that focus on obedience to Allah SWT, not in the preaching style while inspiring to empower Muslim women.